Capitalist Gimmickry in Selected Postmodern Bikol Fiction - Jaucian, Ma. Cienna A. (LIRIP Journal of Interdisciplinary Studies, 2023)
The Bicol Region contributes to the complex definition of Filipino identity amidst globalization and transnational capitalism. Its literature reveals how capitalism has affected the people, who participate in it as members of the global workforce. Sianne Ngai’s Theory of the Gimmick is applied to a postmodern reading of the Bikol short story (osipon) “Cinarding'' by Jay Salvosa, and of selected flash fiction in the chapbook #WeHealAswang by Dennis Gonzaga. Gimmick devices, endemic to late capitalist societies, indicate ambivalence and exploitation. This research shows that the selected postmodern texts are also sites for gimmicks, revealing capitalist mechanisms in a setting outside Ngai’s original scope. Unraveled are both the ordinariness and the extraordinariness of life within a capitalist system and all its ploys, as well as the Bikolnon way of interacting with and responding to them.